Metropolitan structures - Gabriel Loumeau (ETH Zurich, KOF Swiss Economic Institute, 2020)
How does the structure of metropolitan areas a ect urbanization and welfare? Using the development of urban sub-centers in France in the 1970s, I study the short- and long-term e ects of urban structural changes. To retrieve within metropolitan area e ects, I exploit the fact that out of 11 planned subcenters, only 9 have actually been developed. Using local population data between 1926 and 2015, I observe a polarization of growth in favor of sub-centers. As local gains might be o set by losses elsewhere, I develop a general equilibrium model to investigate global e ects. Overall, the observed shift towards polycentric metropolitan structures leads to an increased urbanization (by about 900,000 inhabitants in 2015) and a 0.7% national welfare growth.
hdl:20.500.11850/401648
Keywords: R11; R13; R58; 330; Metropolitan areas; urbanization; structure; growth; mobility